No immediate effect of regulatory reduction of chromium in leather among adult patients with chromium allergy. (17th July 2021) - Alinaghi, Farzad; Thyssen, Jacob P.; Zachariae, Claus; Johansen, Jeanne D.
Abstract: Background: In March 2014, the European Commission issued a new regulation restricting the content of hexavalent chromium (Cr) in leather to no more than 3 mg/kg. We previously performed a questionnaire study in January 2014 to characterize our patients with Cr contact allergy prior to regulatory intervention. Objectives: To assess whether clinical characteristics, self‐reported sources of Cr exposure, and burden of disease changed in patients with Cr allergy over time. Methods: A questionnaire study was performed among 172 adult dermatitis patients with Cr allergy and 587 age‐ and sex‐matched dermatitis patients without Cr allergy. A questionnaire was sent to all dermatitis patients patch tested from 2003 to 2018 in August 2019. Results: The overall response rate was 61.2% (759/1241). Patients with Cr allergy were still more commonly affected by current foot dermatitis (odds ratio [OR] 3.82, 95% confidence interval [CI] 2.07‐7.08) and hand dermatitis (OR 1.98, 95% CI 1.13‐3.49) compared with controls diagnosed during 2013 to 2018. The proportion of patients with Cr allergy reporting dermatitis caused by leather exposure did not change during 2003 to 2012 vs 2013 to 2018 (71.0% vs 66.2%, P  = .5). Furthermore, estimates on occupational performance and disease severity (eg, current dermatitis), number of anatomical locations with dermatitis, worst‐case dermatitis, and effect on work were similar in patients with Cr allergy for 2003 to 2012 vs 2013 to 2018. Conclusion: No immediate sign of improvement was found in patients with Cr allergy concerning severity of disease and dermatitis from leather exposures 5 years after adoption of the regulation against hexavalent Cr in leather. The regulation may have to be revised for better protection of those already sensitized.